A new genus and three new species of leafhopper tribe Scaphoideini (Hemiptera: Cicadellidae: Deltocephalinae) from India with a note on Gunghuyana cingalensis Distant - Viraktamath, C.a.; Yeshwanth, H.m. (Zootaxa, 2020)
Advikus gen. nov. and three new species, Advikus siddappaji sp. nov. (type species, India: Karnataka), A. andamanicus sp. nov. (India: Andaman & Nicobar Islands) and A. radhamaniae sp. nov. (India: Karnataka) are described and illustrated. A key to the known genera of the tribe Scaphoideini from the Indian subcontinent and also the three new species are provided. A lectotype for Gunghuyana cingalensis Distant is designated and the female type is redescribed and illustrated.